Applying comic strip media in Pancasila and civic education to improve student learning outcomes at Malaysian school - Eva Aprilia Yustanti; Afiful Ikhwan; Devid Dwi Erwahyudin (JPP (Jurnal Pendidikan dan Pembelajaran), 2025)
Pancasila and Civic Education learning is often considered less interesting by students, especially when the delivery of material is abstract and monotonous. This can have an impact on students' low interest in learning, motivation, and learning outcomes. To overcome these challenges, comic strip media was introduced as an innovative approach that aims to create a more interesting, interactive, and easy-to-understand learning atmosphere. This study aims to explore the application of comic strip media in learning to improve student learning outcomes in SB Ampang Malaysia. Using a descriptive qualitative approach, data was collected through interview, observation, and documentation techniques. Data analysis is carried out including data reduction, data presentation, and conclusion drawing and verification. The main informants in this study include teachers, students, and learning program managers. The results of the study showed that the use of comic strip media had a positive impact on learning. Comic strips that contain visual illustrations and story narratives that are relevant to Pancasila and Civic Education materials help students understand Pancasila values, civic and national character more concretely. In addition, this media also increases students' active involvement in classroom activities such as discussions, questions and answers, and simple comic creation projects. Comic strips are able to foster interest in learning, trigger motivation and develop students critical thinking skills. Students become more confident in expressing opinions and showing enthusiasm in participating in learning. The measurement of learning outcomes in the context of qualitative research is carried out through observation of changes in student behavior, reflective interviews, and analysis of student learning outcomes. Cognitive, affective and psychomotor aspects were assessed holistically based on student activity, material understanding, attitude towards lessons, and skills in expressing material content through visual media. Thus, comic strip media can be used as an innovative and effective alternative learning strategy, especially in the context of education for the children of Indonesian migrant workers in Malaysia. The use of this media should be expanded and developed in various subjects and receive support through teacher training to be more optimal in its design.